2015
DOI: 10.1126/science.aaa5945
|View full text |Cite
|
Sign up to set email alerts
|

The mutagenic chain reaction: A method for converting heterozygous to homozygous mutations

Abstract: An organism with a single recessive loss-of-function allele will typically have a wild-type phenotype while individuals homozygous for two copies of the allele will display a mutant phenotype. Here, we develop a method that we refer to as the mutagenic chain reaction (MCR), which is based on the CRISPR/Cas9 genome editing system for generating autocatalytic mutations to generate homozygous loss-of-function mutations. We demonstrate in Drosophila that MCR mutations efficiently spread from their chromosome of or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
531
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 542 publications
(559 citation statements)
references
References 7 publications
8
531
2
4
Order By: Relevance
“…With few exceptions (Hoffmann et al 2011), the practicality of such introductions has been limited by the lack of a means to ensure the spread of the engineered genetic material through a population. In a recent article, Gantz and Bier (2015) describe the mutagenic chain reaction (MCR), an approach that employs the CRISPR/Cas9 system to drive a mutation to high frequency in a population, making gene replacement at the population level practical for any species that can be made to accept a transgene in the laboratory.There is, in fact, an extensive literature on "gene drive" systems that can transform entire populations (reviewed in Sinkins and Gould 2006, Gould 2008, and Burt 2014 and going back to Curtis 1968and Foster et al 1972. The work of Burt and colleagues (Burt 2003;Deredec et al 2008;North et al 2013) considering the population genetics of homing endonucleases as a means to transform entire populations is particularly relevant, and much of what we describe below is a specific application of the general principles developed earlier and applied to MCR.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With few exceptions (Hoffmann et al 2011), the practicality of such introductions has been limited by the lack of a means to ensure the spread of the engineered genetic material through a population. In a recent article, Gantz and Bier (2015) describe the mutagenic chain reaction (MCR), an approach that employs the CRISPR/Cas9 system to drive a mutation to high frequency in a population, making gene replacement at the population level practical for any species that can be made to accept a transgene in the laboratory.There is, in fact, an extensive literature on "gene drive" systems that can transform entire populations (reviewed in Sinkins and Gould 2006, Gould 2008, and Burt 2014 and going back to Curtis 1968and Foster et al 1972. The work of Burt and colleagues (Burt 2003;Deredec et al 2008;North et al 2013) considering the population genetics of homing endonucleases as a means to transform entire populations is particularly relevant, and much of what we describe below is a specific application of the general principles developed earlier and applied to MCR.…”
mentioning
confidence: 99%
“…With few exceptions (Hoffmann et al 2011), the practicality of such introductions has been limited by the lack of a means to ensure the spread of the engineered genetic material through a population. In a recent article, Gantz and Bier (2015) describe the mutagenic chain reaction (MCR), an approach that employs the CRISPR/Cas9 system to drive a mutation to high frequency in a population, making gene replacement at the population level practical for any species that can be made to accept a transgene in the laboratory.…”
mentioning
confidence: 99%
“…But less than a year later, developmental biologist Ethan Bier of the University of California, San Diego, and his student Valentino Gantz reported that they had designed just such a system in fruit flies 7 . Bier and Gantz had used three layers of boxes to contain their flies and adopted lab safety measures usually used for malaria-carrying mosquitoes.…”
Section: Top 5 Patent Applicantsmentioning
confidence: 99%
“…Beaucoup moins vont audelà pour analyser les conséquences biologiques des modifications introduites. Parmi les réalisations les plus significatives dans le domaine biomédical voici quelques exemples spectaculaires donnés dans l'ordre chronologique : -2014 : obtention de réarrangements chromosomiques reproduisant des situations observées en oncologie 23 ; -2015 : élaboration de la méthode MCR (Mutagenic Chain Reaction) où une modification hétéro-zygote agit en trans de manière autocatalytique pour obtenir l'homozygotie en court-circuitant la transmission mendélienne 24 . Ce procédé d'abord validé chez la Drosophile a été appliqué chez l'Anophèle vecteur de l'agent du paludisme.…”
Section: Pas De Crispation Terminologique Autour Du Terme « éDition »unclassified